(untitled) (Texas Journal of Engineering and Technology, 2022)
This article presents the results of a study to determine the effects of groundwater on the mechanical properties of an aluminum alloy. The corrosion was evaluated on this aluminum alloy that was subjected to an aqueous solution attack from a four-point extractor at a depth of (4-4.5) meter in an area west of Baghdad. The results indicated that the addition of silicon carbide nanoparticles improved the properties. The mechanical strength of the base alloy, especially at a ratio 2.0 wt.%, significantly reduced the rate of pitting